GDP Data Revisions and Forward-Looking Monetary Policy in Switzerland - Thomas J. Jordan; Peter Kugler; Carlos Lenz; Marcel R. Savioz (University of Basel, Center of Business and Economics (WWZ), 2005)
This paper analyzes forward-looking rules for Swiss monetary policy in a small structural VAR model consisting of four variables taking into account data revisions for GDP. First, the paper develops an analytical method to analyze the effect of data revision errors in GDP on the ex ante or conditional inflation-output-growth volatility trade-off and applies it to Swiss data. Second, the effects of different targets in a forward-looking monetary policy on ex post or unconditional volatility of inflation and output growth is explored by a simulation exercise. In general, the results obtained suggest that focusing monetary policy on GDP growth instead on inflation may lead to an inefficient policy with both increased medium term inflation and GDP growth volatility in the presence of GDP data revisions.
Keywords: E52; E58; 330; Structural VAR; forward-looking monetary policy; efficiency frontier; GDP data revisions